ICE manual of construction law - Ramsey, Vivian (ICE manuals., 2011)
Written for those without legal training, by acknowledged experts from within the construction industry and specialist construction law firms, the most important construction law issues are addressed: from planning, financing and procurement, through operational issues and general law, to claims and dispute resolution.